2021
DOI: 10.5812/semj.113359
|View full text |Cite
|
Sign up to set email alerts
|

Public Views on Priority Groups for COVID-19 Vaccination: A Survey from Iran

Abstract: Background: In the initial coronavirus disease 2019 (COVID-19) vaccination program, prioritizing vulnerable groups is inevitable due to limited supply. Currently, most of the allocation strategies are focused on individuals’ characteristics. Objectives: The present study aimed to assess the opinions of Iranian population in specifying high-priority individuals and groups for COVID-19 vaccination. Methods: An online survey was conducted using some popular social media in Iran. The data was collected from Irania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…These groups were currently prioritized for vaccination by Iranian health policymakers. The results were similar to those found by Moradi et al, who surveyed 878 Iranians about priority groups for vaccination [14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These groups were currently prioritized for vaccination by Iranian health policymakers. The results were similar to those found by Moradi et al, who surveyed 878 Iranians about priority groups for vaccination [14].…”
Section: Discussionsupporting
confidence: 91%
“…However several studies have examined the tendency to receive vaccines, preference for domestic versus non-Iranian vaccines [13], priority groups for vaccination [14], and adverse effects of vaccine [15] among special groups in Iran. These issues, along with other factors affecting attitudes, are comprehensively addressed in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Paloyo et al (16) pointed out that for the Philippines and some other countries with limited supply, the elderly may not always be prioritized. Moradi et al (17) used an online survey to assess Iranian population's views on priority individuals and groups for COVID-19 vaccination. They found that healthcare workers, high-risk patients, and the elderly were prioritized vaccination groups.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With vaccination of the people, new hopes for the disease control were created. But, there are still different challenges, including non-complete, low coverage of vaccination, insufficient immunity in the communities ( Maserat et al, 2021 ; Moradi et al, 2021 ), and emerging and spreading new variants in the world, such as Delta ( Alexandar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%